2011
DOI: 10.1073/pnas.1010890108
|View full text |Cite
|
Sign up to set email alerts
|

Skint-1 is a highly specific, unique selecting component for epidermal T cells

Abstract: αβ T-cell repertoire selection is mediated by peptide-MHC complexes presented by thymic epithelial or myeloid cells, and by lipid-CD1 complexes expressed by thymocytes. γδ T-cell repertoire selection, by contrast, is largely unresolved. Mice mutant for Skint-1, a unique Ig superfamily gene, do not develop canonical Vγ5Vδ1 + dendritic epidermal T cells. This study shows that transgenic Skint-1, across a broad range of expression levels, precisely and selectively determines the Vγ5Vδ1 + dendritic epidermal T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 33 publications
6
161
0
Order By: Relevance
“…44,45 The restricted but mandatory implication of CD277 in the activation of particular human ␥␦ T-cell subsets brings to mind the mandatory role played by Skint-1, another member of the extended B7 receptor family, in the selection of murine intraepidermal ␥␦ T cells. [16][17][18] Although Skint-1 deficiency prevents differentiation of T cells expressing invariant V␥5V␦1 TCR, it has no effect on other ␥␦ or ␣␤ T-cell compartments. Whether Skint-1 directly interacts with V␥5V␦1 TCR or modulates TCR engagement by yet undefined antigens remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 The restricted but mandatory implication of CD277 in the activation of particular human ␥␦ T-cell subsets brings to mind the mandatory role played by Skint-1, another member of the extended B7 receptor family, in the selection of murine intraepidermal ␥␦ T cells. [16][17][18] Although Skint-1 deficiency prevents differentiation of T cells expressing invariant V␥5V␦1 TCR, it has no effect on other ␥␦ or ␣␤ T-cell compartments. Whether Skint-1 directly interacts with V␥5V␦1 TCR or modulates TCR engagement by yet undefined antigens remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The mandatory role played by Skint-1 in the intrathymic positive selection and functional maturation of the murine intraepidermal V␥5V␦1 T-cell subset raises questions about the general role played by Skint1-related receptors in the selection and activation of ␥␦ T cells in mice and other species. [16][17][18][19] Although there are 10 intact skint1 paralogs in the mouse, the only human skint1 ortholog is a pseudogene. The human proteins with the greatest similarity to the extracellular domain of murine Skint-1 are the BTNs.…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports suggested that antigen experienced γδ T cells, which had received ligand-dependent TCR signals, mature as IFNγ producers, while antigen naïve cells differentiate towards the γδ17 lineage 9 . Furthermore, in the past decade, there have been several reports debating the importance of different degrees of TCR signaling in the generation of γδ17 cells 1013 . The signal strength hypothesis asserts that the quantity of the signal downstream of the TCR can direct lineage choice 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This 2-D assay is easy to perform, highly efficient and sensitive, allowing analysis at the single cell level. However, it neither supports T cell development beyond the stage of DP nor the generation of γδ DETC 13 , both of which require direct interactions with the thymic epithelium.…”
Section: Representative Resultsmentioning
confidence: 99%